Evaluation of a cooling/heating-assisted microextraction instrument using a needle trap device packed with aminosilica/graphene oxide nanocomposites, covalently attached to cotton. Issue 11 (14th May 2018) - Ghiasvand, A. R.; Heidari, N.; Abdolhosseini, S.; Hamdi, A.; Haddad, P. R.
Abstract : Evaluation of the first commercial sample of a cooling/heating-assisted microextraction instrument. Abstract : A low-cost and reliable cooling/heating-assisted microextraction (CHaME) instrument was designed and fabricated for use in different modes of microextraction methods. The CHaME setup is able to cool down the sorbent and simultaneously heat the sample in a wide temperature range. Consequently, it can create a large thermal gap between the sorbent and the sample matrix, to promote the release of analytes from the sample tissue and enhance their effective trapping on the microextraction phase. The primary versions of the instrument have previously been evaluated, coupled with different modes of solid- and liquid-phase microextraction strategies. Compared with conventional microextraction systems, it is able to extract volatile organic compounds from complicated solid matrices more effectively, rapidly and without any need for a sample preparation step. In this research, the final and compact version of the CHaME instrument was fabricated and employed in a cooling/heating-assisted needle trap device (CHaME-NTD) for microextraction of polycyclic aromatic hydrocarbons (PAHs) in contaminated soil samples, prior to GC-FID determination. An aminosilica/graphene oxide nanocomposite was synthesized, covalently attached to cotton (Am-Si/GO/Cot), packed inside a needle, and applied as an effective sorbent for trapping of the analytes. The influence of experimental parameters on the extraction efficiency of the TC-NTD-GC-FID strategy was evaluated and optimized. Under the optimal conditions, linear dynamic ranges (LDRs), limits of detection (LODs), and relative standard deviations (RSDs) for the PAHs were 0.001–2.0 μg g −1, 5–38 pg g −1, and 6.2–9.8% ( n = 6), respectively. The CHaME-NTD-GC-FID procedure was compared with the traditional NTD-GC-FID method. Additionally, the Am-Si/GO/Cot nanocomposite sorbent was compared with the most frequently used commercial sorbents. The results demonstrated the remarkable performance of the CHaME-NTD procedure and the Am-Si/GO/Cot composite sorbent. The developed setup was also used for the extraction and determination of PAHs in contaminated soil samples, through the CHaME-NTD-GC-FID procedure.